(untitled) (Fiep Bulletin - online, 2011)
The objective of the present study was to analyze the dermatoglyphics of 18 hypertensive women (primary hypertension) as discretionary parameter for the analysis of the effects of the physical endurance in the arterial blood pressure (BP) of the hypertensive ones at rest before exercise, during exercise and after a 4 hours rest. The sample space of this study was 2000 individuals who have hypertension (HT), being 68.50% or 1370 female, who have been attended by the Municipal Medical Facility of Santarém city– BRAZIL. The sample was composed by 200 hypertensive individuals. This way, nearly 14.60% or 18 hypertensive individuals, in the age bracket from 40 to 48 years, all females, are the objective of this study. All have been participated freely, as an experimental group, being determinate by 06 individuals with genetic marker (dermatoglyphic) whorl (W), 06 with arch (A) and 06 loops (L). The exercises had the intensity of 60-80% of the HRmáx, 03 times a week, during 03 months, 60 min long, 13 sessions. All hypertensive females had effective use of 100% in the frequency. SBP and DBP MAP, HRrest, HRrexer and HR of returning to calm have been analyzed. The main analyzed variables have shown Means and Deviation Pattern/ of Whorl group (W) SBP125 ± 2.2; DBP 81±1.1; MAP 96 ± 1.4; HRrest 66.7±5.7; HRrexer 128 ± 2.9. Loops (L) SBP 126±2.9; DBP 82±1.0 MAP 97±1.5; HRrest. 62.2±4.4; HRrexer 117±3.5. Arch (A) SBP 124±2.6; DBP 80±2.3; MAP 94±2.3; HRrest 63.3±7.5; HRrexer. 126±2.2. The general physical condition of each individual have been verified through the evaluation and revaluation of the following components: DSBP Peak; DSBPrest and VO2máx (ET); HRrest, HRmáx (ECG) that a substantial improvement of the physical conditioning by the analysis of the studied variables has been occurred.